Pseudo-convex mixtures generated by shape-extended stable distributions for extremes. (2nd April 2016) - Santos, Rui; Felgueiras, Miguel; Paulo Martins, João
ABSTRACT: A shape-extended definition of min-stable (and max-stable) laws is provided and applied to obtain pseudo-convex mixtures. The main properties of the obtained class of distributions are derived, and a particular case generated by the exponential distribution is investigated.